Pulsed electromagnetic fields and platelet rich plasma alone and combined for the treatment of wear-mediated periprosthetic osteolysis: An in vivo study. (1st September 2018) - Veronesi, F.; Fini, M.; Sartori, M.; Parrilli, A.; Martini, L.; Tschon, M.
Graphical abstract: Abstract: Wear-mediated osteolysis is a common complication occurring around implanted prosthesis, which ultimately leads to bone loss with mechanical instability and the need for surgical revision. At the moment, revision surgery is the only effective treatment. The aim of this study was to assess the efficacy of pulsed electromagnetic fields (PEMFs) and platelet rich plasma (PRP), alone and in association, in a clinically relevant in vivo model of periprosthetic osteolysis. Titanium alloy pins were implanted intramedullary in distal femurs of male inbred rats and, after osseointegration, polyethylene particles were injected intra-articularly to induce osteolysis. Animals were divided in four groups of treatment: PEMFs, PRP, PEMFs + PRP and no treatment. Microtomography was performed during the course of experiments to monitor bone stock and microarchitecture. Histology, histomorphometry, immunohistochemistry and biomechanics were evaluated after treatments. Biophysical and biological stimulations significantly enhanced bone to implant contact, bone volume and bone microhardness and reduced fibrous capsule formation and the number of osteoclasts around implants. Among treatments, PEMFs alone and in association with PRP exerted better results than PRP alone. Present data suggest that biophysical stimulation, with or without the enrichment with platelet derived growth factors, might be a safe, mini-invasive and conservative therapy for counteracting osteolysis and prompting bone formation around implants. Statement of significance: Pulsed electromagnetic fields (PEMFs) and platelet rich plasma (PRP) show anabolic and anti-inflammatory effects and they are already been used in clinical practice, but separately. To date, there are no preclinical in vivo studies evaluating their combined efficacy in periprosthetic osteolysis, in bone tissue microarchitecture and in biomechanics. The aim of the present study was to evaluate the effects of PEMFs and PRP in vivo, when administered individually and in combination in the treatment of periprosthetic wear mediated ostelysis, and in restoring the osteogenetic properties of perimplant bone tissue and its biomechanical competence. The combination of PEMFs and PRP could be employed for counteracting the ostelysis process in a conservative and non surgical manner.